Wysoka krótkowzroczność jako objaw patognomoniczny w zespole Sticklera - Mrugacz, Malgorzata; Średzińska-Kita, Dorota; Bakunowicz-Łazarczyk, Alina; Piszcz, Małgorzata (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Stickler’s syndrome is an autosomal dominant inherited disorder of connective tissue related to incorrect collagen structure. The changes include ocular, hearing, and joint and bone abnormalities. We present a case of 6-years-old patient with Stickler’s syndrome, with characteristic features.